International Capital Markets : Developments, Prospects, and Key Policy Issues 1997. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1997)
Provides a comprehensive survey of recent developments in international financial markets, including developments in emerging capital markets, bond markets, major currency markets, and derivative markets. The report focuses on efforts by the major industrial countries to strengthen the management of financial risk and prundential oversight over the international banking system. It also critically evaluates existing mechanisms for international cooperation of financial supervision and regulation and proposes the development of international banking standards.